CASP8 intronic expansion identified by poly-glycine-arginine pathology increases Alzheimer’s disease risk - Lien Nguyen; Ramadan Ajredini; Shu Guo; Lisa E. L. Romano; Rodrigo F. Tomas; Logan R. Bell; Paul T. Ranum; Tao Zu; Monica Bañez Coronel; Chase P. Kelley; Javier Redding-Ochoa; Evangelos Nizamis; et al. (Proceedings of the National Academy of Sciences, 2025)
Alzheimer’s disease (AD) affects more than 10% of the population ≥65 y of age, but the underlying biological risks of most AD cases are unclear. We show anti-poly-glycine-arginine (a-polyGR) positive aggregates frequently accumulate in sporadic AD autopsy brains (45/80 cases). We hypothesize that these aggregates are caused by one or more polyGR-encoding repeat expansion mutations. We developed a CRISPR/deactivated-Cas9 enrichment strategy to identify candidate GR-encoding repeat expansion mutations directly from genomic DNA isolated from a-polyGR(+) AD cases. Using this approach, we isolated an interrupted (GGGAGA) n intronic expansion within a SINE-VNTR-Alu element in CASP8 ( CASP8 -GGGAGA EXP ). Immunostaining using a-polyGR and locus-specific C-terminal antibodies demonstrate that the CASP8 -GGGAGA EXP expresses hybrid poly(GR)n(GE)n(RE)n proteins that accumulate in CASP8 -GGGAGA EXP (+) AD brains. In cells, expression of CASP8 -GGGAGA EXP minigenes leads to increased p-Tau (Ser202/Thr205) levels. Consistent with other types of repeat-associated non-AUG (RAN) proteins, poly(GR)n(GE)n(RE)n protein levels are increased by stress. Additionally, levels of these stress-induced proteins are reduced by metformin. Association studies show specific aggregate promoting interrupted CASP8 -GGGAGA EXP sequence variants found in ~3.6% of controls and 7.5% AD cases increase AD risk [ CASP8 -GGGAGA-AD-R1; OR 2.2, 95% CI (1.5185 to 3.1896), P = 3.1 × 10 −5 ]. Cells transfected with a high-risk CASP8 -GGGAGA-AD-R1 variant show increased toxicity and increased levels of poly(GR)n(GE)n(RE)n aggregates. Taken together, these data identify polyGR(+) aggregates as a frequent and unexpected type of brain pathology in AD and CASP8 -GGGAGA-AD-R1 alleles as a relatively common AD risk factor. Taken together, these data support a model in which CASP8 -GGGAGA EXP alleles combined with stress increase AD risk.